The impact of increasing workload on academics: Is there time for quality teaching? - Dixon, Kathryn; Dixon, Robert; Scott, Shelleyann (AARE, 2007)
This paper reports on the results of an investigation into the impact of increasing workloads in higher education on teaching quality. Thirty eight academic staff in a Western Australian university were interviewed on a number of issues related to the increasing hard managerialism evident in their work environment as well as other issues associated with the changing nature of organisational culture. The results indicated that the sample believed there were mixed messages emerging from the university administration regarding the importance of teaching. The available reward structures including job security were perceived to be focussed on the research agenda rather than good teaching. The research has revealed that although the majority of those interviewed perceived themselves as having positive attitudes towards their teaching, this did not always translate into time spent on effective preparation and delivery. With increasing pressure placed upon the higher education sector we may be facing a crisis of confidence with the quality of teaching in our universities as we move further into the 21st century.